(untitled) (Itinera, 2023)
This paper is based on the experience gained in European funded research projects. Despite the different objectives pursued by each project, the thread that connects them is the relationship between the performing arts and urban regeneration, in order to emphasise the importance of directly involving the territory and its inhabitants in urban regeneration processes. The research that has matured in the field of territorial co-design at national and European level was based on the conviction that the ultimate goal of urban renewal is not exclusively the quality and safety of life. In fact, the processes of urban renewal, when viewed from the perspective of social and cultural innovation, produce a collective participatory experience capable of overcoming the dichotomy between the public and private dimensions, guiding processes of ’commoning’ (Chatterton 2010) or the preservation of the ’common good’, which here takes the form of the production of relational goods, of community constructions (Manzini 2021). The aim of this essay is therefore to develop, within the framework of sociology, a reflection on the impact and value of culture in the context of urban renewal processes. The proposal is thus to re-read urban renewal from a culturalist perspective. To this end, it is important to define what cultural sociology studies as a theoretical premise in order to understand how important social practises and cultural participation are in defining social imaginaries and in defining related life, such as housing, consuming, producing, just to name a few areas. Therefore, shifting urban renewal to a participatory key, here I mean citizen participation through artistic practise, allows us to question models of individual and collective well-being, also in terms of well-being, which I believe must be at the heart of urban planning and design processes, in order to recognise the multidimensionality inherent in renewal and open new multidisciplinary paths.